Propuesta mejoramiento de las condiciones lumínicas y acústicas de la Universidad Antonio Nariño sede Bucaramanga (2020)
This project proposes strategies to improve lighting and acoustics at the Antonio Nariño University in Bucaramanga block A in search of adequate comfort for the population that carries out their daily learning activities there. The first step was a survey of the current state, which would take into account the morphology of the building, the materials in the finishes and furniture, to be digitized in the software Dialux Evo (lighting), RADIT 2D (acoustics) inIn this way we can obtain a diagnosis with which to propose improvement strategies that will also be represented by the software mentioned above, with the necessary changes in materials thus to reach the necessary lighting and acoustic comfort for the development of the various activities taking place in the classrooms.